2020
DOI: 10.1002/ptr.6860
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of herbal medicine for cancer‐related fatigue in lung cancer survivors: A systematic review and meta‐analysis

Abstract: Approximately half of lung cancer patients (LCP) receiving chemotherapy are experiencing cancer‐related fatigue (CRF). In East Asia, herbal medicines (HMs) have been used as tonics due to their anti‐fatigue effect. This systematic review evaluated the effectiveness and safety of HMs for CRF in LCP. We comprehensively searched 12 electronic medical databases to search randomized controlled trials (RCTs) and quasi‐RCTs investigating HMs for CRF in LCP, published up to September 2019. The primary outcome was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A systematic review by Kwon et al assessed the effectiveness and safety of herbal medicines for cancerinduced fatigue in 861 lung cancer patients. It has been observed that herbal medicines combined with conventional medicine significantly improved fatigue levels, quality of life, and activities of daily living compared to traditional medicine alone (18).…”
Section: Targeting Reactive Oxygen Species Signalingmentioning
confidence: 99%
“…A systematic review by Kwon et al assessed the effectiveness and safety of herbal medicines for cancerinduced fatigue in 861 lung cancer patients. It has been observed that herbal medicines combined with conventional medicine significantly improved fatigue levels, quality of life, and activities of daily living compared to traditional medicine alone (18).…”
Section: Targeting Reactive Oxygen Species Signalingmentioning
confidence: 99%
“…At present, although there is no direct evidence for the usage rate of CHM in the treatment of post-viral fatigue, but in the past few decades, it has been widely used in clinic and achieved certain results in the treatment of cancer-related fatigue (CRF) and chronic fatigue syndrome (CFS). Evidence suggests that CHM can clearly decreased 1.77 scores in fatigue scale-14 (FS-14) scores as an adjuvant or monotherapy for CFS [ 22 ] and significantly lowered 1.47 scores in Brief Fatigue Inventory (BFI) global score for CRF [ 23 ]. Meanwhile take Ginseng for example [ 24 ], up to now, various clinical practice and animal-based experiments have already confirmed the safe anti-fatigue effects of Ginseng Radix et Rhizoma, as well as its components.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitations and lack of evidence of conventional medicines available for the prevention and/or management of respiratory symptoms caused by PM, complementary and alternative medicine (CAM) and herbal medicine treatment strategies have garnered increased interest. Several systematic reviews on the effects of herbal medicines for respiratory diseases, such as COPD, asthma, and lung cancer, have been published [14][15][16]. However, there are few studies on lung disease induced by PM.…”
Section: Introductionmentioning
confidence: 99%